The CGIAR micronutrients project: justification, history, objectives, and summary of findings - Bouis, Howarth E.; Graham, Robin D.; Welch, Ross M. (International Food Policy Research Institute, 1999)
In this paper, the authors describe a strategy of breeding plants that enrich themselves, that load high amounts of minerals and vitamins into their edible parts, has the potential for substantially reducing recurrent costs that are associated with other strategies, such as fortification and supplementation. However, they caution that this approach will be successful only if farmers are willing to adopt such varieties, if the edible parts of these varieties are palatable and acceptable to consumers, and if the incorporated micronutrients can be absorbed by the human body. In examining the feasibility of a plant breeding strategy, five core questions were posed: 1) Is it scientifically feasible to breed for staple food varieties whose seeds are micronutrient-dense? 2) What effect will breeding for micronutrient-dense seeds have on plant yields and will farmers adopt such varieties? 3) Will breeding for micronutrient-dense seeds change the processing or consumer characteristics of staple foods? 4) Will micronutrient intakes be increased to a significant degree and to what extent will the extra micronutrients in staple foods consumed be bioavailable? 5) Are there other lower-cost, more easily sustainable strategies for reducing micronutrient malnutrition? The authors argue that the time is long overdue for involving agricultural research directly in the fight against micronutrient malnutrition. Because trace minerals are important not only for human nutrition, but for plant nutrition as well, plant breeding holds great promise for making a significant, low-cost, and sustainable contribution to reducing micronutrient, particularly mineral, deficiencies in humans, and may have important spinoff effects for increasing farm productivity in developing countries in a way that is environmentally-beneficial. They conclude by reporting that results so far obtained under the CGIAR Micronutrient Project indicate that the breeding parameters are not difficult and are highly likely to be low cost.